Analysis of main failure pattern using discrete Fourier transform on metal‐epoxy‐based adherent‐laminates. Issue 6 (13th May 2015) - Niederwimmer, Karin; Kieberger, Benjamin; Hassel, Achim Walter
<x xml:space="preserve">Abstract</x> Sandwich‐structured materials are widely used in science, industry and consumer products and therefore have to fulfil several parameters of the designed application, but in particular mechanical stability. This article focuses on mechanical testing of composite sandwich‐structured laminates, consisting of metal and epoxy‐based adherent. As peel forces denote enormous strains for adhesives, floating roller method was used to determine the mechanical stability of the laminates. Besides the peel resistance, the main failure pattern is also of interest as it has an influence on the long‐term stability of the laminates. Therefore, the curves of mechanical testing were investigated using discrete Fourier transform (DFT) to give an indication of the predominating failure mechanism. The samples themselves were analysed using light microscopy to validate the results of the DFT.